Right Of Immunity Of Members Of The House Of Representatives (Case Study Of Immunity Rights Of Langkat Regency DPRD Members) - Haris Kelana Damanik; Kusbianto Kusbianto; Ariman Sitompul (International Asia Of Law and Money Laundering, 2023)
Paradiqma democracy demands that every form of legislation and various decisions get the approval of the people's representatives and as much as possible attention to the interests of the people. Although the authority to form a law is in the hands of the DPR together with the president and does not involve the sovereign holder, namely the people in the process of its formation, but currently the role of the people in influencing a policy to produce a law and to assess the implementation of a law cannot be underestimated. The research aims to provide immunity rights for members of Parliament/DPRD as public officials in terms of carrying out their duties and authorities. The research method used in this research is normative juridical law research by using the approach of legislation and doctrine applied to a legal problem and is prescriptive that is expected to be applied in society. The results of the study concluded that members of the DPR / DPRD in performing their duties and authorities need to be protected properly and honorably in accordance with the level of Honor as elected representatives of the people and each member of the DPR must also reflect the personal and behavior of the honorable and leading in law enforcement.